Multiloop control for fast transient DC–DC converter - Zhou, Mi (2020)
A novel ac coupled feedback (ACCF) is proposed to alternatively realize fast transient response while inherently controlling the start-up in-rush current of a dc-dc switching converter. The proposed ACCF is modified from a conventional capacitor multiplier and connected between the outputs of the converter and the transconductance. With this supplemental feedback, the transient response has been significantly improved due to the gain-boosting effect around the compensator's midband. Moreover, the ACCF circuit assists to manage the ramping speed of the output voltage during power-up, thereby eliminating the bulky soft-start circuit. The new controller is very simple to implement and occupies a tiny footprint on-chip. A buck converter with the proposed scheme has been fabricated using the 0.18-μm standard CMOS process with an active silicon area of 0.573 mm 2 . Measurement results show that the output voltage rises linearly for a soft-start period of 1.05 ms according to the designed slope. Excellent load transient responses are achieved under different load current steps; the output voltage overshoot/undershoot of 60 mV settles down within 10 μs for a load variation from 50 μA to 1 A in 1 μs. Moreover, the proposed converter maintains both excellent load and line regulations of 0.018 mV/mA and 0.0056 mV/mV, respectively.